Method to improve the performance of network time delay of EPA system - Ning LIU; Chong-quan ZHONG; Yao-yao LIN (Tongxin xuebao)
In order to improve the performance of network-induced time delay of EPA (Ethernet for plant automation) networked control systems, the interacting mechanism between the control and the communication in EPA system was studied and EPA-CS (EPA cooperative scheduling) method was presented. Through setting their mutually cooperative time slices for function blocks that executed the control tasks and data transmission that executed the communication tasks, and through determining the executing time and frequencies of control tasks in their time slices, the method could accomplish the cooperation between control tasks and communication tasks in EPA system. When the round scanning cy-cles of devices are very little or there are many function blocks that need network communication in system, the method can effectively reduce the network load to improve the performance of network-induced time delay of EPA system.